Correlation between status of benzimidazole resistance in Haemonchus contortus on bio and molecular assays - MAHARSHI, A K; SWARNKAR, C P; SINGH, D; MANOHAR, G S (The Indian Journal of Animal Sciences, 2011)
In relation to benzimidazole resistance in Haemonchus contortus, the diversity in genotypes was established through allele specific-polymerase chain reaction in infective larvae (L3) of sheep from different agroclimatic regions of Rajasthan. The results of molecular assay were correlated with results obtained on biological assay (faecal egg count reduction test and egg hatch assay). The study was conducted in 22 sheep flocks and a total of 691 L3 was genotyped for benzimidazole resistance. The overall genotypic frequency for homozygous resistant (rr) larvae ranged from 72.22% (north-eastern region) to 96.87% (eastern region) in farm flocks and from 61.79% (north-eastern region) to 95.83% (eastern region) in field flocks. The results of correlation revealed that phenotypic expression of benzimidazole resistance on faecal egg count reduction test was evident with occurrence of >30% rr genotypes in population. Likewise presence of >30% r alleles in population were found to express the benzimidazole resistance on egg hatch assay. With decrease in faecal egg count reduction%, there was a linear increase in the frequency of ‘rr’ genotype in population with maximum of ‘rr’ genotype (96.58%) in flocks exhibiting <50% efficacy for benzimidazole on faecal egg count reduction test.